Pengaruh Konsentrasi Ekstrak Etanol Kulit Manggis (Garcinia Mangostana Linn) Terhadap Daya Hambat Pertumbuhan Bakteri Lactobacillus Acidophilus (Kajian In Vitro) - Fatmala, Rona, drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K), drg. Retno Sari (2015)
Background: The mangosteen rind was known as the best natural source of xanthone and had antibacterial compound such as, flavonoids, tannins, saponins, alkaloids and triterpenoid so expected to inhibit the growth of Lactobacillus acidophilus, one of the bacteria that caused dental caries. Objective: The purpose of this research was to know the effect of ethanol extract of mangosteen rind in inhibiting the growth of Lactobacillus acidophilus. Methods: This study was laboratoris experimental research with post test only control group design. Methods used in antibacterial test was the diffusion of Cup-plate Technique method. The test was divided into 6 groups of treatment. The group was the ethanol extract of mangosteen rind concentration of 10%, 20%, 40%, 80%, Chlorhexidine 0.2% for positive control and aquadest for negative control. Antibacterial sensitivity tests for extract of mangosteen rind against Lactobacillus acidophilus was evidenced by measuring the magnitude of the resistance zone formed on the MRS Agar. Data analysis was using one way ANOVA test followed by Post Hoc LSD analysis test. Results: The concentration of ethanol extract of mangosteen rind which was most powerful in inhibiting Lactobacillus acidophilus was the concentration of 80%, whereas the minimum concentration of ethanol extract of mangosteen rind in inhibiting Lactobacillus acidophilus was the concentration of 10%. Conclusion: The ethanol extract of mangosteen rind was able to inhibit Lactobacillus acidophilus with a concentration of at least 10% and the most intense concentration of ethanol extract of mangosteen rind was 80%. One way ANOVA test and Post Hoc LSD test suggested that there was a meaningful difference between each treatment groups.